METODE MA’NA CUM MAGHZA DALAM MEMAHAMI AYAT-AYAT DZIKIR - Azizah Arisa Wijaya, Nadiah (Khulasah : Islamic Studies Journal, 2025)
The essence of human creation is to worship and serve Allah. In addition to prayer, many forms of worship lead humans to continually depend on Allah SWT, one of which is dhikr. Dhikr is a form of worship that can be performed anytime and anywhere without any hindrance. While prayer may be obstructed by several factors, this does not apply to dhikr. Even women in a state of nifas (postpartum period) and menstruation are not prohibited from constantly remembering Allah SWT. However, the peoples do not understand this essence. Therefore, in this study, the author will present the interpretation of dhikr verses and examine the benefits and virtues contained in these verses using the Ma’na cum Maghza approach. This research aims to provide an understanding of the virtues and benefits of dhikr. This study is a library research that takes data and information from various materials in the library, such as books, magazines, documents, notes, historical stories, and others. The method used is descriptive analysis, which describes matters related to dhikr and the Ma’na cum Maghza theory obtained from primary sources such as Tafsir al-Munir, Tafsir al-Qurtubi, Tafsir al-Misbah, as well as related books and literature. Then, an analysis is conducted on the dhikr verses that have been described, by interpreting the Qur'anic verses and explaining all aspects contained in them, such as the meaning of words, asbabun nuzul (reasons for revelation), according to the steps used in the Ma’na cum Maghza theory. At the end of the discussion, this study concludes that dhikr has many meanings and different purposes. Among them, there is the intention to remember Allah when the time for prayer arrives, to remember Allah by contemplating the nature and all forms of His creation, and the context of remembering Allah during prayer. With this theory, many ways of remembering Allah are found to increase our faith in Him and strengthen our Aqeedah and Tawheed in Allah SWT.